2016
DOI: 10.1515/jbcpp-2015-0063
|View full text |Cite
|
Sign up to set email alerts
|

Biflavonoid fraction from Garcinia kola seed ameliorates hormonal imbalance and testicular oxidative damage by anti-tuberculosis drugs in Wistar rats

Abstract: Kolaviron protects male reproductive system from oxidative damage by anti-tuberculosis drugs via the antioxidative mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Data from the current study showed that the body, testes, and epididymal weights were significantly lower in STZ-induced diabetic rats than the nondiabetic control group (Figures 3-6). These findings are in agreement with previous studies that also demonstrated a significant decrease in body, testicular, and epididymal weights in diabetic rats [5,18,27,28,33,45,47]. Moreover, variations in animal body and organ weights have been reported to affect spermatogenesis, sperm quality, and sperm concentration [5,18,27,28,33,45,47].…”
Section: Evaluation Of Rat Body Testicular and Epididymal Weights Ssupporting
confidence: 93%
See 4 more Smart Citations
“…Data from the current study showed that the body, testes, and epididymal weights were significantly lower in STZ-induced diabetic rats than the nondiabetic control group (Figures 3-6). These findings are in agreement with previous studies that also demonstrated a significant decrease in body, testicular, and epididymal weights in diabetic rats [5,18,27,28,33,45,47]. Moreover, variations in animal body and organ weights have been reported to affect spermatogenesis, sperm quality, and sperm concentration [5,18,27,28,33,45,47].…”
Section: Evaluation Of Rat Body Testicular and Epididymal Weights Ssupporting
confidence: 93%
“…In other studies, KV restored antioxidant enzymes in the testes of diabetes-induced rats [5,49]. The protective effect of KV observed in the testes and epididymis of diabetic rats might either be due to the inhibition of glycation by the antioxidant enzymes or scavenging abilities of ROS, thus decreasing the formation of LPO [5,[27][28][29][30].…”
Section: Assessment Of Antioxidant Enzymes In the Testicular And Epidmentioning
confidence: 96%
See 3 more Smart Citations